Associação da acepromazina com propofol em tartarugas-da-amazônia Podocnemis expansa criadas em cativeiro - Alves-Júnior, José Roberto Ferreira; Bosso, Andréa Cristina Scarpa; Andrade, Mariana Batista; Jayme, Valéria de Sá; Werther, Karin [UNESP]; Santos, André Luiz Quagliatto (My University, 2012)
Purpose: To evaluate the effects of different concentrations of an anesthetic association in giant amazon turtles (Podocnemis expansa). Methods: Twenty healthy P. expansa of both sexes weighing between 1.0 and 1.5kg commercially bred in the Araguaia River Valley, Goias, Brazil, were separated into two groups (G1 n=10 and G2 n=10). Each group received a respective protocol: P1= acepromazine (0.5 mg/kg IM) and propofol (5 mg/kg IV) and P2 = acepromazine (0.5 mg/kg IM) and propofol (10 mg/kg IV). The acepromazine was administered in the left thoracic member and the propofol in the cervical vertebral sinus. Assessments were made of the anesthetic parameters of locomotion, muscle relaxation, response to pain stimuli in the right thoracic and pelvic members and heartbeat. Results: The anesthetic induction time was the same for both protocols (P1 and P2); however the P2 effects were of a longer duration. Conclusion: The sedation achieved with both protocols (P1 and P2) were satisfactory for the biological sample collection, physical examinations and minor surgeries on this species.
Association of acepromazine with propofol in giant amazon turtles Podocnemis expansa reared in captivity
Keywords: Acepromazine; Anesthesia; Propofol; Reptiles; Turtles